Enriched antibacterial and antifouling performance of organoclay filled hybrid epoxy composites. (April 2021) - Sabu, M.; Vinse Ruban, Y. Jaya; Raja, P.; Mon, S. Ginil; Muthukrishnan, S.
Abstract: Organically changed montmorillonite (OMMT) can significantly enhance the surface property of composite blends. In this present work, for the first time we have reported the enhanced antifouling performance on the substrate, combined with cured epoxy (CE), unsaturated polyester (UP), and organically changed montmorillonite (OMMT) blends. The newly developed CE-UP-OMMT materials were submerged into the real time marine environment with the other samples of glass, plastic, fibre (broadly used in the ship hull), and wood. Since the contact angle is increased, the surface energy is decreased to the epoxy toughened blend incorporated with clay and thus showing enhanced antibacterial and antifouling properties. It provides promising results in 1 and 3 wt% clay incorporated epoxy with 10 wt% UP composite blends which improved antibacterial and antifouling performance during the microbial and macro-fouling activity in the real-time marine environment for around three months. In the future, these blends could be new opportunities for the marine industry. Graphical abstract: Image 1 Highlights: The modified Epoxy-UP-OMMT blend having the improved anti-biofouling property. The epoxy composite blend directly crosslinks with clay and maintain excellent anti-biofouling performance for >3 months in the real-time marine environment. Possessing high in fouling release in 1 and 3 wt% clay incorporated epoxy with 10 wt% UP samples composites blends.